The impact of a training program on developing level of kindergarten educator’s knowledge of Learning Disabilities A semi-experimental study in Lattkia - شروف, انساب (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aimed to measure the impact of a training program in developing kindergarten educator’s knowledge in Learning Disabilities. The semi-experimental approach was followed and a cognitive test was used as a research tool. The research sample consisted of (20) kindergarten educator, who were drawn by the intentional sampling method. The training program consisted of five training unites, and 20 training hours, and the researcher used (TPS) strategy. The results of the research revealed the existence of a large impact size of (2.01) of the program in developing the level of the sample in Learning Disabilities. The results also showed that the average scores of the experimental group members after training program was clearly higher than theirs before the application.